2016
DOI: 10.1001/jamapsychiatry.2016.1031
|View full text |Cite|
|
Sign up to set email alerts
|

Whole-Body Hyperthermia for the Treatment of Major Depressive Disorder

Abstract: clinicaltrials.gov Identifier: NCT01625546.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
77
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 17 publications
5
77
1
3
Order By: Relevance
“…Since a large body of literature implies that serotoninergic activity is strongly related to impulsive and aggressive behavior 16, 17, 20, 34 , it is reasonable to suggest that changes in serotonin transporter density modify the incidence of violent behavior, and that seasonal effects of solar radiation influence both. Recent studies indicate that, in animals, whole-body heating activates subdivisions of the dorsal raphe nucleus implicated in mood regulation, and whole-body warming has a substantial antidepressant effect in humans 35 . It is plausible that when temperature rises, people go out more and meet other people, which increases the rate of violent incidents.…”
Section: Discussionmentioning
confidence: 99%
“…Since a large body of literature implies that serotoninergic activity is strongly related to impulsive and aggressive behavior 16, 17, 20, 34 , it is reasonable to suggest that changes in serotonin transporter density modify the incidence of violent behavior, and that seasonal effects of solar radiation influence both. Recent studies indicate that, in animals, whole-body heating activates subdivisions of the dorsal raphe nucleus implicated in mood regulation, and whole-body warming has a substantial antidepressant effect in humans 35 . It is plausible that when temperature rises, people go out more and meet other people, which increases the rate of violent incidents.…”
Section: Discussionmentioning
confidence: 99%
“…First, careful (theoretical) interpretation of data is a dire necessity and not just relying on automatic 9 Although some have suggested that full-body warmth treatments can be effective against psychopathologies (Janssen et al, 2016), others have voiced their criticisms (Fried, 2016), and rightfully so. Social Thermoregulation Therapy is not just about warmth, but by associating warmth with predictability in the right social situations.…”
Section: The Risks Of Relying On Big Data and Further Ethical Concernsmentioning
confidence: 99%
“…Frequent sauna bathing has also been shown to be associated with a reduced risk of dementia and Alzheimer's disease [17] and reduces the symptoms of depression [18]. Other passive heat therapies such as Waon therapy, infrared saunas, and whole-body hyperthermia have also been shown to relieve stress and improve the symptoms of psychiatric disorders such as depression and anxiety [18][19][20].…”
Section: Introductionmentioning
confidence: 99%